151k views
2 votes
3(3m - 2) -3 =36 step by step​

User Lutz
by
5.0k points

2 Answers

2 votes
first distribute the 3 to the 3m and -2. now u have 9m - 6 - 3 = 36. combine -6 and -3 and u get -9. 9m - 9 =36. add 9 to both sides, so now u have 9m=45. divide by 9 and u get m=5. hope this helped!
User Marsh
by
5.1k points
4 votes

Answer:

Step-by-step explanation: Alright so first you ditribute the 3 with 3m and - 2 so you will get 9m - 6 - 3 = 36 from there add all like terms like - 6 and - 3 so you will get 9m - 9 = 36 now we want variables in one side and normal numbers in the others so we add 9 to both sides so we get 9m = 45 now divide both by 9 so M = 5

User DoronK
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.